Legitimacy in European Administrative Law: Reform and Reconstruction - Ruffert, M. (European Administrative Law Series, 2011)
Legitimacy in European Administrative Law: Reform and Reconstruction. Edited by Matthias Ruffert; Acknowledgements; Contents; Chapter 1. Legitimacy in Administrative Law: Reform and Reconstruction by Pascale Gonod; Chapter 2. Legitimacy in Administrative Law? A French Perspective by Jacques Caillosse; Chapter 3. People as 'Users' and 'Citizens'. The Quest for Legitimacy in British Public Administration by Andrew Le Sueur; Chapter 4. Legitimacy and Accountability as a Basis for Administrative Organisation and Activity in Germany by Eberhard Schmidt-Aßmann